Portrait of a Western Australian Artist: Vlase Zanalis - Yiannakis, John (Flinders University, 2007)
This paper was originally given as a PowerPoint presentation. It highlights particular aspects of Vlase Zanalis' work, notably his landscape and Aboriginal themes, helping to show his ability to operate in three different spiritual domains: Orthodoxy, Christian Science and Aboriginal spirituality.